The Right To Freedom Of Movement – A Fundamental Right Of Person In The Light Of National And International Regulations - Coman, Varvara (Acta Universitatis Danubius. Juridica, 2022)
Both at the national and international level, the right to freedom of movement has attracted the attention of specialists in the field of law and beyond, representing a factor of progress in the development of the human personality. Initially, the recipients were the individuals considered individually (as economic agents or service providers) so that, gradually, the freedom of movement was extended to the level of legal principle, to the idea of a citizen of the European Union. The freedom of movement is the foundation of the idea of a common European space without internal barriers and has been regulated both by the provisions of the legislation of the European Union and of the member states.